INTRODUCTION OF PRESCHOOL AND PRIMARY SCHOOL AGE CHILDREN TO SOCIAL AND LEGAL NORMS - Maryambibi Abdullayeva Djumaniyazovna (Galaxy International Interdisciplinary Research Journal, 2022)
One of the most important tasks today is to actively involve preschoolers and younger schoolchildren in the process of social relations, to teach them how to effectively organize interpersonal communication. Their successful adoption of social and legal norms is of particular importance in order to make them active participants in this process. It is known that interaction between people is based on certain social and legal norms. In many cases, the process of relationships, governed by social and legal norms, also serves to express the level of culture of the participants.Behavior in public places, visiting cinemas, catering, consumer services, using public transport, and observance of traffic rules reflect the general culture of the individual.